2020
DOI: 10.1093/imrn/rnz313
|View full text |Cite
|
Sign up to set email alerts
|

Sonine Formulas and Intertwining Operators in Dunkl Theory

Abstract: Let V k denote Dunkl's intertwining operator associated with some root system R and multiplicity k. For two multiplicities k, k ′ on R, we studybetween Dunkl operators with multiplicities k and k ′ . It has been a long-standing conjecture that V k ′ ,k is positive if k ′ ≥ k ≥ 0. We disprove this conjecture by constructing counterexamples for root system Bn. This matter is closely related to the existence of Soninetype integral representations between Dunkl kernels and Bessel functions with different multiplic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The proofs of Theorems 5.11 and 5.15 are based on analysis for multivariable hypergeometric functions which are given in terms of Jack polynomial expansions in the sense of [Kan,M3], combined with methods of Sokal [So] and a variant of the Shanbhag principle from [CL]. We finally mention that the generalized Wallach set (1.4) plays also an interesting role in connection with integral representations of Sonine type between Bessel functions for root system B n and the positivity of intertwining operators in the B n case, see [RV3].…”
Section: Introductionmentioning
confidence: 99%
“…The proofs of Theorems 5.11 and 5.15 are based on analysis for multivariable hypergeometric functions which are given in terms of Jack polynomial expansions in the sense of [Kan,M3], combined with methods of Sokal [So] and a variant of the Shanbhag principle from [CL]. We finally mention that the generalized Wallach set (1.4) plays also an interesting role in connection with integral representations of Sonine type between Bessel functions for root system B n and the positivity of intertwining operators in the B n case, see [RV3].…”
Section: Introductionmentioning
confidence: 99%
“…then Formula (29) coincides with the definition of the fractional derivative given by Letnikov (28). In Reference [9], Sonine concluded that his formula cannot coincide with Grünwald-Letnikov formula for α > 0 without adding auxiliary function.…”
Section: Sonine's Fractional Derivative and Integralmentioning
confidence: 64%
“…This formula was analyzed by Letnikov in his answer [7] on the remarks by Sonine. Letnikov proved that, under assumption that the function f is (m + 1) = ([α] + 1)-times continuously differentiable inside the circle γ, Formula (29) coincides with Letnikov's Formula (28). Note that Letnikov discussed Sonine's Formula (29) under the stronger assumptions on the function f .…”
Section: Sonine's Fractional Derivative and Integralmentioning
confidence: 99%
See 2 more Smart Citations